ChemInform Abstract: Enantio‐ and Diastereoselective Synthesis of Highly Substituted Benzazepines by a Multicomponent Strategy Coupled with Organocatalytic and Enzymatic Procedures. Issue 23 (10th June 2014) - Moni, Lisa; Banfi, Luca; Basso, Andrea; Galatini, Andrea; Spallarossa, Martina; Riva, Renata
Abstract Enantiomerically pure 4, 5‐dihydro‐1H‐benzo[c]azepines with three contiguous stereogenic centers are assembled with a good control of diastereoselectivity.